Association Between Triglyceride Glucose Index with Cognitive Impairment and Dementia in Adult Population: A Meta-Analysis - Han, Yuqing; Meng, Xu; Wang, Dahui (Hormone and Metabolic Research, 2024)
The current understanding of the correlation between insulin resistance (IR) and cognitive dysfunction is limited. Therefore, the objective of this systematic review and meta-analysis was to assess the association between the triglyceride glucose (TyG) index, a recently suggested indicator of IR, and cognitive impairment and dementia in the adult population. Observational studies pertinent to our research were identified through comprehensive searches of the PubMed, Embase, and Web of Science databases. To account for potential heterogeneity, the random-effects models were employed to aggregate the findings. This meta-analysis included ten observational studies involving 5602409 participants. Compared to those with the low TyG index, subjects with the high TyG index were significantly associated with the risk of cognitive impairment [risk ratio (RR): 1.39, 95% confidence interval (CI): 1.22 to 1.59, p<0.001; I2=45%) and dementia (RR: 1.30, 95% CI: 1.06 to 1.60, p=0.01; I2=50%). The association was consistent for Alzheimer’s disease (RR: 1.35, 95% CI: 1.04 to 1.76, p=0.03; I2=54%) and vascular dementia (RR: 1.18, 95% CI: 1.13 to 1.24, p<0.001; I2=0%). Subgroup analyses showed that the association between TyG index with cognitive impairment and dementia were stronger in cross-sectional studies than that in cohort studies (p for subgroup difference=0.02), but not significantly modified by age, sex, or diabetic status of the participants. In conclusion, a high TyG index may be associated with higher risk of cognitive impartment and dementia in adult population.
Keywords: triglyceride glucose index; cognitive impairment; dementia; meta-analysis; insulin